2015
DOI: 10.1016/j.canlet.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle delivery of an SN38 conjugate is more effective than irinotecan in a mouse model of neuroblastoma

Abstract: Neuroblastoma (NB) is the most common and deadly solid tumor in children. The majority of NB patients have advanced stage disease with poor prognosis, so more effective, less toxic therapy is needed. We developed a novel nanocarrier-based strategy for tumor-targeted delivery of a prodrug of SN38, the active metabolite of irinotecan. We formulated ultrasmall-sized ( < 100 nm) biodegradable poly(lactide)-poly(ethylene glycol) based nanoparticles (NPs) containing SN38 conjugated to tocopherol succinate (SN38-TS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Our results in the GD2-low PDX model, showing similar activity of GD2-targeted NPs and control NPs, suggest that active targeting with 3F8-NPs was likely to be more critical than the EPR effect to achieve prolonged drug exposure in our neuroblastoma PDX models. Other authors have shown that tocopherol succinate-conjugated SN-38, loaded in non targeted PLA-PEG NPs (<100 nm), improved the activity of systemic irinotecan in neuroblastoma xenografts and accumulated in tumors due to the EPR effect [12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results in the GD2-low PDX model, showing similar activity of GD2-targeted NPs and control NPs, suggest that active targeting with 3F8-NPs was likely to be more critical than the EPR effect to achieve prolonged drug exposure in our neuroblastoma PDX models. Other authors have shown that tocopherol succinate-conjugated SN-38, loaded in non targeted PLA-PEG NPs (<100 nm), improved the activity of systemic irinotecan in neuroblastoma xenografts and accumulated in tumors due to the EPR effect [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, novel formulations of SN-38 prodrugs designed for intravenous (i.v.) administration showed higher efficacy in neuroblastoma xenografts [12, 13]. In other cancers, SN-38-loaded self-assembly nanoparticles (NPs) have consistently outperformed irinotecan [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have been used to encapsulate a wide variety of poorly water-soluble drugs, leading to dramatic improvements in their solubility, stability and drug-targeting properties, as well as reducing any adverse effects. [10][11][12][13] Furthermore, nanoparticles-based drug delivery systems can preferentially target tumors by taking advantage of the enhanced permeability and retention (EPR) effect. 14) A broad range of drug delivery systems, including PEGylated conjugates, polymer micelles, liposome formulations and dendrimers, have been extensively investigated for the formulation of SN-38 to improve its water solubility and bioavailability.…”
mentioning
confidence: 99%
“…This compound has been found to inhibit the proliferation of various cancer cells in vitro and in vivo, [20][21][22][23][24][25][26] including cervical cancer cells, breast cancer cells, prostate cancer cells, gastric cancer cells, and so on. TOS, a mitochondria-targeting drug, has the synergic effect on nuclear DNA-damaging drugs such as CDDP.…”
mentioning
confidence: 99%